The Conception of Restorative Justice in Actualization of the Indonesian Criminal Justice System - Roy Rovalino Herudiansyah; Pujiyono Pujiyono; Nur Rochaeti (Budapest International Research and Critics University, 2022)
The purpose of this study is to study and analyze the actualization of restorative justice in the Indonesian criminal justice system. In this writing, the author uses normative juridical methods with research specifications in the form of descriptive analysis. Based on the discussion of the weaknesses of the Indonesian criminal justice system, the criminal justice system tends to be emotional in punishing perpetrators. An overly positivist understanding places the law as an absolute rule in order to achieve legal certainty and disregard the expediency and justice of the law for perpetrators and victims of a criminal justice legal system that tends to override the rights of defendants or suspects and victims. Restorative justice is a way of resolving cases through legal processes outside the courts that aim to achieve justice that emphasizes the recovery of the condition of the perpetrator and victim. Recovery is defined as recovery to the victim as well as the perpetrator. So what is restored is not just the victim. The position of restorative justice in Indonesia is strictly regulated in various laws and regulations such as the 1945 Constitution of the Republic of Indonesia; Law Number 48 of 2009 concerning Judicial Power, Law Number 14 of 1985 as amended by Law Number 5 of 2004 as last amended by Law Number 3 of 2009 concerning the Supreme Court.